Data for Tropical Legumes Cluster Evaluation - International Crops Research Institute for the Semi-Arid Tropics; International Center for Tropical Agriculture; Inter-American Institute for Cooperation on Agriculture; CGIAR; Mathematica (2023)
This dataset presents data used in the analysis published in the Final Report for the "Tropical Legumes Cluster Evaluation". CGIAR staff and their contractors collected the following survey data as part of the Tropical Legumes (TL) project, funded by the Bill & Melinda Gates Foundation. The TL project invested $67 million in modernizing legume breeding, seed production and distribution, and variety promotion systems throughout sub-Saharan Africa and South Asia. This file contains cleaned and coded survey data from TL surveys in four segments: (1) common bean in Tanzania, (2) groundnut in Tanzania, (3) groundnut in Nigeria, and (4) cowpea in Nigeria. CGIAR partners conducted these surveys from 2016 to 2017 to measure farmer adoption of improved TL-promoted varieties, as well as the effect of adoption on yields and income. Samples are locally and regionally defined in the case of common bean in Tanzania and groundnut in Nigeria, but nationally representative of legume farmers in the case of groundnut in Tanzania and cowpea in Nigeria. This work was funded by the Bill & Melinda Gates Foundation.